Measurements of evaporated aluminium concentration on self-absorbed spectral lines - Lobko, A.K.; Trubchaninov, S.A.; Tsarenko, A.V. (Вопросы атомной науки и техники, 2002)
In the paper we discuss the experimental results of powerful plasma-stream interaction with aluminum target at the presence of the magnetic field. The plasma streams are generated by a quasi-stationary plasma accelerator (QSPA Kh- 50). Such experiments performed with QSPA facility during last years [1-3] are of great interest for current disruption simulation in ITER tokamak and testing divertor materials. Some experimental series in our activity were devoted to the problem of mass losses of target under the high power plasma stream irradiation. This work presents the spectral method of determination of the evaporated material quantities in plasma-target interaction experiments. The distinctive feature of the offered work is follows – all spectral measurements were carried out using aluminum spectral lines only. There are two mechanisms of mass losses – evaporation and splashing melt layer. We succeeded in the evaluation of the evaporation mechanism contribution to the mass defect for aluminum target.